Economic models of tropical deforestation : - Kaimowitz, David (Center for international forestry research, 1998)
This book reviews the results and methodology of over 150 of these models and synthesizes the main lessons that can be learned from them. Higher agricultural prices, lower wages, less off-farm employment, and more roads generally lead to more deforestation. Major doubts remain on the impact of technological change, agricultural input prices, household incomes, and tenure security. The role of macro level factors such as population growth, poverty reduction, national income levels, economic growth and foreign debt is still largely uncertain.